2015
DOI: 10.1007/s00268-015-2975-y
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome Between Hepatic Resection and Transarterial Embolization for Hepatocellular Carcinoma More Than 10 cm: A Propensity Score Model

Abstract: HR had significantly better 5 year survival than TAE for patients with HCC ≥ 10 cm in the propensity score model. Overall survival of BCLC stage B may be improved by considering HR as first treatment option for resectable large HCCs, provided patient is fit for surgery with good liver remnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…This is similar or slightly superior to the survival rates reported by several recent studies from both Eastern and Western countries . Although LR for huge HCC is associated with poorer outcomes compared to LR for smaller tumors, it remains the best treatment option for this group of patients as it provides the best survival outcomes compared to other modalities such as transarterial embolization . Concordant with previous studies , we found microvascular invasion, R1 resection, and elevated AFP to be independent prognostic factors of RFS and hepatitis B positivity, tumor rupture, and R1 resection as independent prognostic factors of OS after LR for huge HCC.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is similar or slightly superior to the survival rates reported by several recent studies from both Eastern and Western countries . Although LR for huge HCC is associated with poorer outcomes compared to LR for smaller tumors, it remains the best treatment option for this group of patients as it provides the best survival outcomes compared to other modalities such as transarterial embolization . Concordant with previous studies , we found microvascular invasion, R1 resection, and elevated AFP to be independent prognostic factors of RFS and hepatitis B positivity, tumor rupture, and R1 resection as independent prognostic factors of OS after LR for huge HCC.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, our main objective was to identify preoperative predictors of early (<1 year) mortality from disease recurrence with special emphasis on the role of inflammatory indices such NLR, PLR, and PNI. Identification of preoperative prognostic factors is especially important in selecting appropriate candidates for surgery, especially, for patients with huge HCC due to their poorer long‐term survival after LR and the increased postoperative mortality rate . Although, LR for huge HCC is a technically challenging high‐risk procedure , recent improvements in surgical technique, such as the introduction of the anterior approach and hanging maneuver, have resulted in decreased blood loss and better perioperative outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Отсутствие показаний к резекционному лечению ГЦР при размерах опухоли 10 см и более в большинстве национальных и международных рекомендаций побуждает к дальнейшему изучению этой проблемы. Авторы из Chang Gung Memorial Hospital (Тайвань) при изучении 192 пациентов показали, что резекция печени возможна и обеспечивает достоверно лучшую выживаемость по сравнению с ТАХЭ при размерах опухоли >10 см на фоне цирроза печени класса В и С по СТР в сопоставимых группах (пятилетняя выживаемость 51,5% по сравнению с 3,3%) [26].…”
Section: гепатоцеллюлярный ракunclassified